Comparison of mathematical models to estimate live weight through heart girth in growing Pelibuey sheep - Jorge-Rodolfo Canul-Solís; Rodrigo Portillo-Salgado; Ricardo-A . García-Herrera; Epigmenio Castillo-Gallegos; Luis-Enrique Castillo-Sanchez; Enrique Camacho-Perez; Antonio-Leandro Chaves-Gurgel; Carolina Marques-Costa; Patrick Bezerra-Fernandes; Alfonso-Juventino Chay-Canul (Revista Colombiana de Ciencias Pecuarias, 2022)
Background: Assessment of animal growth based on live weight (LW) in traditional sheep production systems is limited by the high cost of purchase and maintenance of livestock scales. Objective: To develop and evaluate equations for LW prediction using heart girth (HG) in growing Pelibuey sheep. Methods: A dataset (n=415) of clinically healthy male Pelibuey sheep from two months to one year of age, with an average LW of 25.96 ± 10.25 kg and HG of 68.31 ± 10.53 cm, were used. Three equations were evaluated: LW (kg) = −37.70 + 0.93 × HG (Eq. 1); LW (kg) = −1.74 + 0.19 × HG + 0.008 × HG2 (Eq. 2); and LW (kg) = 0.003 × HG2.68 (Eq. 3). Results: The correlation coefficient between LW and HG was r = 0.94 (p<0.001). The three equations showed a high concordance correlation coefficient (CCCs≥0.97). However, the random error was the main component of the mean square partition of the prediction error (≥82.78%) only for Eqs. 1 and 2. The test for parameter identity (intercept=0; slope=1) was accepted only for Eq. 2 (p>0.05). On the other hand, for Eqs. 1 and 3 the intercept was different from zero and the slope was different from one (p<0.05). Conclusion: The second-degree equation accurately and precisely estimated body weight of growing Pelibuey sheep using the HG as a sole predictor variable.